THE INFLUENCE OF EMPLOYEE COMPETENCE AND CORPORATE CULTURE ON THE PERFORMANCE OF MANAGEMENT AT PT. PLN (PERSERO) UNIT INDUK WILAYAH (UIW) SULUTTENGGO - Verel Mawei; James D. D. Massie; Ferdinand J. Tumewu (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2023)
Human resources is one of the most important factors in running an organization because the success or failure of an organization is determined by the effectiveness and efficiency (performance) of its human resources. To determine that employees have high performance, it is certainly inseparable from the role of employee competencies and corporate culture. This study discusses the influence of employee competencies and corporate culture on performance of management at PT. PLN (Persero) Unit Induk Wilayah Suluttenggo. In this study, there are 33 employees who are all in Low-Level Management positions, so 33 samples were taken as research samples. This research is quantitative research using multiple linear regression analysis. The results show that competence has insignificant impact on performance of management, while corporate culture has a positive and significant impact on performance of management. Competence and Corporate Culture simultaneously have a positive and significant impact on Performance of Management.   Keyword: competence, corporate culture, performance of management